Controller Tuning With Evolutionary Multiobjective Optimization : A Holistic Multiobjective Optimization Design Procedure /: A Holistic Multiobjective Optimization Design Procedure. (2016) - Meza, Gilberto Reynoso; Blasco Ferragud, Xavier (Francesc Xavier), 1966-; Sanchis Saez, Javier; Herrero Durá, Juan Manuel
No abstract available